A scandium-containing composite spinel aggregate and its preparation method
By adding scandium oxide and iron oxide to spinel aggregate to replace part of the chromium, a scandium-containing composite spinel aggregate was prepared, which solved the problems of short service life and environmental pollution of magnesium-chromium spinel refractories and achieved a high-performance, low-cost refractory material solution.
Patent Information
- Application Number
- CN202510320990.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-11-14
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Existing magnesium chromium spinel refractory materials have difficulty extending their service life effectively after use and have high processing costs. They also pose a significant risk of hexavalent chromium pollution, and existing patents have failed to effectively reduce chromium content and environmental risks.
By adding scandium oxide to spinel aggregate, combined with iron oxide and aluminum oxide, a portion of the chromium content is replaced, thus preparing scandium-containing composite spinel aggregate, which improves corrosion resistance and reduces chromium content.
It significantly extends the service life of refractory materials, reduces the environmental pollution risk and disposal cost of waste materials, and maintains excellent corrosion resistance in high-temperature environments.
Abstract
Description
Technical Field
[0001] This invention relates to the field of metallurgical technology, and more specifically, to a scandium-containing composite spinel aggregate and its preparation method. Background Technology
[0002] Spinel materials are widely used in refractory materials fields such as copper smelting, cement kilns, and steel refining due to their excellent properties. Among them, magnesia-chromium spinel exhibits superior corrosion resistance in copper smelting and steel refining processes, outperforming other types of spinel (such as magnesia-alumina spinel and iron spinel), making it difficult to replace with other refractory materials. However, if the hexavalent chromium in magnesia-chromium spinel refractories is directly dumped into the environment without treatment, it will pollute groundwater and harm human health. In addition, the cost of treating hexavalent chromium in waste refractory materials is high, and it falls under the category of hazardous waste disposal. Therefore, extending the service life of chromium-containing spinel refractories while reducing the proportion of chromium in refractory materials has become an important issue that urgently needs to be addressed.
[0003] The research by Ni Guolong et al. details the application of magnesia-chrome bricks in copper smelting. Studies show that appropriately increasing the chromium content can significantly improve the copper slag resistance of magnesia-chrome bricks, thereby extending their service life. However, high-chromium-content magnesia-chrome bricks have higher disposal costs after disposal and pose a greater potential environmental pollution risk.
[0004] While Chinese patent CN106966708A mentions the addition of rare earth elements during the production of magnesium-aluminate-carbon bricks, it does not mention the addition of scandium. Furthermore, the spinel content in that patent differs significantly from that of this patent. Chinese patent CN107473730A describes a relatively lower firing temperature and application temperature, a lower spinel content, and no scandium oxide added.
[0005] Therefore, there is an urgent need to provide a high-performance, low-chromium-content scandium-containing composite spinel aggregate and its preparation method to meet the high-performance requirements of modern industry for refractory materials, while reducing environmental risks and processing costs. Summary of the Invention
[0006] The purpose of this invention is to overcome the aforementioned deficiencies in existing technologies and provide a scandium-containing composite spinel aggregate and its preparation method. This invention employs an innovative formulation design, significantly improving the chemical resistance of the spinel aggregate by adding scandium oxide, thereby effectively extending the aggregate's service life. Furthermore, this invention further optimizes the material's chemical composition by introducing some iron oxide and aluminum oxide to replace some of the chromium content in traditional magnesium-chromium spinel. This improvement not only retains the excellent corrosion resistance of spinel aggregate under high-temperature environments but also significantly reduces the amount of chromium used, minimizing the potential environmental pollution risk of hexavalent chromium in waste refractory materials, while also reducing the processing costs of waste refractory materials and improving the material's economic viability and sustainability.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows:
[0008] A method for preparing scandium-containing composite spinel aggregate includes the following steps:
[0009] (1) Mix Sc2O3 powder, fused magnesia, brown fused alumina powder, high chromite powder and limonite powder for 20 min-30 min, add additives and mix again for 30 min-1 h until the mixture is uniform to obtain a wet material; the proportion of the wet material by weight is: 1-3 parts of Sc2O3 powder, 30-40 parts of fused magnesia, 10-20 parts of brown fused alumina powder, 60-80 parts of high chromite powder, 30-50 parts of limonite powder and 0.5-2 parts of additives;
[0010] (2) The wet material is vacuum cast at room temperature until no air bubbles overflow from the casting material. Then the cast device after molding is dried to obtain the dried casting device.
[0011] (3) The dried casting device is calcined at high temperature to obtain the scandium-containing composite spinel aggregate.
[0012] Optionally, in step (1), the absolute purity of the Sc2O3 powder is ≥90%.
[0013] Optionally, in step (1), the particle size of the Sc2O3 powder, fused magnesia, brown corundum powder, high chromium iron ore powder and limonite powder is 74 μm-3 mm.
[0014] Optionally, in step (2), the drying temperature is 100℃-120℃ and the drying time is 24h-48h.
[0015] Optionally, in step (3), the heating rate of the high-temperature calcination is 1℃ / min-5℃ / min, the cooling rate is 1℃ / min-10℃ / min, the constant temperature zone temperature is 1800℃-2100℃, the calcination process is carried out in an inert high-purity argon atmosphere, and the residence time in the constant temperature zone is 6h-48h.
[0016] Optionally, the additive includes at least one of melamine-based, phosphate-based, and silica sol / alumina sol.
[0017] The present invention also discloses a scandium-containing composite spinel aggregate prepared by the above preparation method, wherein the spinel phase ratio in the scandium-containing composite spinel aggregate is ≥95%.
[0018] Optionally, the apparent porosity of the scandium-containing composite spinel aggregate is 2%-5%, and the bulk density is 3.5 g / cm³. 3 -4.7g / cm 3 Compressive strength ≥100MPa, load softening temperature ≥1700℃.
[0019] Implementing the embodiments of the present invention will have the following beneficial effects:
[0020] The scandium-containing composite spinel aggregate of this invention significantly strengthens the grain structure of spinel by adding scandium oxide. The scandium element in scandium oxide is embedded in the spinel lattice in a stable trivalent form, thereby enhancing the overall stability of the material. In traditional high-temperature smelting processes, slag containing high levels of titanium dioxide or cuprous oxide dissolves into the magnesia-chromium spinel structure, leading to decreased corrosion resistance, lower melting point, and consequently shortened service life of refractory bricks. In contrast, the composite spinel aggregate of this invention exhibits lower porosity and superior corrosion resistance. Under the same production process, refractory bricks produced using this aggregate can have a service life 1.2 to 2 times longer than traditional magnesia-chromium spinel refractory bricks when in contact with copper slag and high-titanium smelting slag. Furthermore, this invention further optimizes the chemical composition of the material by introducing some iron oxide and alumina to replace some of the chromium content in traditional magnesia-chromium spinel. This improvement not only preserves the excellent corrosion resistance of spinel aggregate in high-temperature environments, but also significantly reduces the amount of chromium used, thereby reducing the potential environmental pollution risk of hexavalent chromium in waste refractory materials, and lowering the disposal cost of waste refractory materials.
[0021] The scandium-containing composite spinel aggregate of this invention is suitable for various high-temperature smelting scenarios. In steel refining processes, such as in critical areas like sliding gate nozzles and submerged entry nozzles, this aggregate can significantly improve the erosion resistance of refractory materials. Furthermore, it can also be applied to the refining furnace outlet in copper smelting, effectively slowing down the erosion of refractory materials by cuprous oxide, thereby extending the service life of the refractory materials.
[0022] The application effects of this invention have been fully verified. Using scanning electron microscopy (SEM) and other advanced material characterization methods, researchers confirmed the excellent corrosion resistance of the composite spinel aggregate. Experimental results show that this aggregate can effectively resist slag erosion and maintain structural stability under high-temperature environments, thus providing a high-performance, long-life refractory material solution for the high-temperature smelting industry. Detailed Implementation
[0023] The present invention will be further described below with reference to specific embodiments, but this does not limit the present invention in any way.
[0024] Example 1
[0025] The preparation method of scandium-containing composite spinel aggregate in this embodiment includes the following steps:
[0026] (1) Mix Sc2O3 powder with an absolute purity ≥90%, fused magnesia, brown fused alumina powder, high-chromium iron ore powder, and limonite powder for 30 min, then add additives and mix again for 30 min until uniformly mixed to obtain a wet material. The wet material ratio, by weight, is: 1 part Sc2O3 powder, 40 parts fused magnesia, 20 parts brown fused alumina powder, 60 parts high-chromium iron ore powder, 30 parts limonite powder, and 0.5 parts additives to aid in molding. The particle size of Sc2O3 powder, fused magnesia, brown fused alumina powder, high-chromium iron ore powder, and limonite powder is 100 μm-2 mm.
[0027] (2) Vacuum casting of wet material at room temperature until no air bubbles overflow from the casting material, and then drying the molded casting device at 100°C for 48 hours to obtain the dried casting device.
[0028] (3) The dried casting device was calcined at high temperature with a heating rate of 5℃ / min and a cooling rate of 10℃ / min. The constant temperature zone temperature was 1800℃. The calcination process was carried out in an inert high-purity argon atmosphere. The constant temperature zone residence time was 6h to obtain scandium-containing composite spinel aggregate.
[0029] The sintered devices were tested, and scanning electron microscopy and XRD analysis revealed that the spinel phase ratio in the scandium-containing composite spinel aggregate synthesized in this invention reached 96%. The product's properties were also tested: apparent porosity of 5% and bulk density of 3.5 g / cm³. 3 It has a compressive strength of 100 MPa and a load softening temperature of 1721℃. This spinel aggregate is a qualified aggregate and can be used for the further processing of functional refractory materials.
[0030] Example 2
[0031] The preparation method of scandium-containing composite spinel aggregate in this embodiment includes the following steps:
[0032] (1) Mix Sc2O3 powder with an absolute purity ≥90%, fused magnesia, brown fused alumina powder, high chromite powder, and limonite powder for 20 min, then add additives and mix again for 1 h until uniformly mixed to obtain a wet material. The wet material ratio by weight is: 3 parts Sc2O3 powder, 30 parts fused magnesia, 10 parts brown fused alumina powder, 80 parts high chromite powder, 50 parts limonite powder, and 2 parts additives to aid in molding. The particle size of Sc2O3 powder, fused magnesia, brown fused alumina powder, high chromite powder, and limonite powder is 74 μm-1 mm.
[0033] (2) Vacuum casting of wet material at room temperature until no air bubbles overflow from the casting material, and then drying the molded casting device at 120°C for 24 hours to obtain the dried casting device.
[0034] (3) The dried casting device was calcined at high temperature with a heating rate of 1℃ / min and a cooling rate of 1℃ / min. The constant temperature zone temperature was 2100℃. The calcination process was carried out in an inert high-purity argon atmosphere. The constant temperature zone residence time was 48h to obtain scandium-containing composite spinel aggregate.
[0035] The sintered devices were tested, and scanning electron microscopy and XRD analysis revealed that the spinel phase ratio in the scandium-containing composite spinel aggregate synthesized in this invention reached 99.5%. Testing also showed that the product has the following properties: apparent porosity of 2% and bulk density of 4.7 g / cm³. 3 It has a compressive strength of 121 MPa and a load softening temperature of 2100℃. This spinel aggregate is a qualified aggregate and can be used for the further processing of functional refractory materials.
[0036] Comparative Example 1
[0037] The preparation method of the spinel aggregate in this comparative example includes the following steps:
[0038] (1) Mix Sc2O3 powder with an absolute purity ≥90%, fused magnesia, brown fused alumina powder, high-chromium iron ore powder, and limonite powder for 30 min, then add additives and mix again for 30 min until uniformly mixed to obtain a wet material. The wet material ratio, by weight, is: 1 part Sc2O3 powder, 40 parts fused magnesia, 20 parts brown fused alumina powder, 60 parts high-chromium iron ore powder, 30 parts limonite powder, and 0.5 parts additives to aid in molding. The particle size of Sc2O3 powder, fused magnesia, brown fused alumina powder, high-chromium iron ore powder, and limonite powder is 100 μm-2 mm.
[0039] (2) Vacuum casting of wet material at room temperature until no air bubbles overflow from the casting material, and then drying the molded casting device at 100°C for 48 hours to obtain the dried casting device.
[0040] (3) The dried casting device was calcined at high temperature with a heating rate of 5℃ / min and a cooling rate of 10℃ / min. The constant temperature zone temperature was 1750℃. The calcination process was carried out in an inert high-purity argon atmosphere. The constant temperature zone residence time was 6h to obtain scandium-containing composite spinel aggregate.
[0041] The sintered devices were tested, and scanning electron microscopy and XRD analysis revealed that the spinel phase proportion in the scandium-containing composite spinel aggregate synthesized in this comparative example reached 86%. The product's properties were also tested: apparent porosity of 5.6% and bulk density of 3.3 g / cm³. 3 The compressive strength is 98 MPa, and the load softening temperature is 1680℃. Because the temperature in the constant-temperature zone did not reach the minimum required temperature for this product, the spinel phase ratio and other indicators did not meet the requirements, thus affecting its corrosion resistance.
[0042] Comparative Example 2
[0043] The preparation method of the spinel aggregate in this comparative example includes the following steps:
[0044] (1) Mix Sc2O3 powder with an absolute purity ≥90%, fused magnesia, brown fused alumina powder, high chromite powder, and limonite powder for 20 min, then add additives and mix again for 1 h until uniformly mixed to obtain a wet material. The wet material ratio by weight is: 5 parts Sc2O3 powder, 30 parts fused magnesia, 10 parts brown fused alumina powder, 80 parts high chromite powder, 50 parts limonite powder, and 2 parts additives to aid in molding. The particle size of Sc2O3 powder, fused magnesia, brown fused alumina powder, high chromite powder, and limonite powder is 74 μm-1 mm.
[0045] (2) Vacuum casting of wet material at room temperature until no air bubbles overflow from the casting material, and then drying the molded casting device at 120°C for 24 hours to obtain the dried casting device.
[0046] (3) The dried casting device was calcined at high temperature with a heating rate of 1℃ / min and a cooling rate of 1℃ / min. The constant temperature zone temperature was 2100℃. The calcination process was carried out in an inert high-purity argon atmosphere. The constant temperature zone residence time was 48h to obtain scandium-containing composite spinel aggregate.
[0047] The sintered devices were tested, and the scanning electron microscope and XRD showed that the scandium-containing composite spinel aggregate synthesized in this comparative example had a spinel phase ratio of 90%, with a separate scandium oxide phase present. This resulted in a waste of scandium oxide, poor economic efficiency, and failure to meet the requirement of a relatively single phase in the composite spinel.
[0048] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing scandium-containing composite spinel aggregate, characterized in that, Includes the following steps: (1) Mix Sc2O3 powder, fused magnesia, brown fused alumina powder, high chromite powder and limonite powder for 20 min-30 min, add additives and mix again for 30 min-1 h until the mixture is uniform to obtain a wet material; the proportion of the wet material by weight is: 1-3 parts of Sc2O3 powder, 30-40 parts of fused magnesia, 10-20 parts of brown fused alumina powder, 60-80 parts of high chromite powder, 30-50 parts of limonite powder and 0.5-2 parts of additives; (2) The wet material is vacuum cast at room temperature until no air bubbles overflow from the casting material. Then the cast device after molding is dried to obtain the dried casting device. (3) The dried casting device is calcined at high temperature to obtain the scandium-containing composite spinel aggregate.
2. The method for preparing scandium-containing composite spinel aggregate according to claim 1, characterized in that, In step (1), the absolute purity of the Sc2O3 powder is ≥90%.
3. The method for preparing scandium-containing composite spinel aggregate according to claim 1, characterized in that, In step (1), the particle size of the Sc2O3 powder, fused magnesia, brown corundum powder, high chromite powder and limonite powder is 74μm-3mm.
4. The method for preparing scandium-containing composite spinel aggregate according to claim 1, characterized in that, In step (2), the drying temperature is 100℃-120℃ and the drying time is 24h-48h.
5. The method for preparing scandium-containing composite spinel aggregate according to claim 1, characterized in that, In step (3), the heating rate of the high-temperature calcination is 1℃ / min-5℃ / min, the cooling rate is 1℃ / min-10℃ / min, the constant temperature zone temperature is 1800℃-2100℃, the calcination process is carried out in an inert high-purity argon atmosphere, and the residence time in the constant temperature zone is 6h-48h.
6. The method for preparing scandium-containing composite spinel aggregate according to claim 1, characterized in that, The additives include at least one of melamine-based, phosphate-based, and silica / alumina sols.
7. A scandium-containing composite spinel aggregate prepared by the preparation method according to any one of claims 1-6, characterized in that, The scandium-containing composite spinel aggregate contains ≥95% spinel phase.
8. The scandium-containing composite spinel aggregate according to claim 7, characterized in that, The scandium-containing composite spinel aggregate has an apparent porosity of 2%-5% and a bulk density of 3.5 g / cm³. 3 -4.7g / cm 3 Compressive strength ≥100MPa, load softening temperature ≥1700℃.
Citation Information
Patent Citations
Unfired alumina-magnesite carbon brick and preparation method thereof
CN106966708A
Method for preparing fine-crystalline and high-strength magnesia alumina spinel transparent ceramic
CN107473730A
Manufacture of high strength silicon nitride sintered body in high temperature
JP1992077363A
Alumina ceramic articles having cubic spinel on surfaces and methods for preparing alumina ceramic articles and for sintering
US5795362A